2005
DOI: 10.1007/s10926-005-5945-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Persistent Elbow Tendonitis Among Auto Assembly Workers

Abstract: Workers at highest risk for persistent elbow tendonitis should be placed at jobs with lower repetition levels and that use more neutral wrist postures. Effective interventions must address both the ergonomic and psychosocial risk factors in a multifaceted approach to this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…The correspondence has been moderate, even though the strain index identified more hazardous jobs than the HAL method (74,75). An association with upper-limb disorders has been seen in several cross-sectional studies (75,78,83,84) as well as in prospective longitudinal studies (85)(86)(87)(88)(89)(90). The intra-and inter-observer repeatability has been moderate to good (82,91).…”
Section: The American Conference Of Governmental Industrial Hygienistmentioning
confidence: 89%
“…The correspondence has been moderate, even though the strain index identified more hazardous jobs than the HAL method (74,75). An association with upper-limb disorders has been seen in several cross-sectional studies (75,78,83,84) as well as in prospective longitudinal studies (85)(86)(87)(88)(89)(90). The intra-and inter-observer repeatability has been moderate to good (82,91).…”
Section: The American Conference Of Governmental Industrial Hygienistmentioning
confidence: 89%
“…tennis, golf, and baseball, cf. Priest et al, 1977) and daily activities such as meat processing, woodcutting, shoemaking, and glassblowing (Vukovic et al, 2004;Werner et al 2005), where workers are required to undertake repetitive or forceful tasks. Kurppa et al (1991) found the incidence of epicondylitis in a meat-processing factory was up to 11 times greater than the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Epicondylitis was defined as self-reported pain at either epicondyle area on 2 or more days in the previous month and one of the following on exam: presence of pain at the lateral epicondyle with resisted active wrist extension, pain at the medial epicondyle with resisted active wrist flexion, or tenderness to palpation over the medial and lateral epicondyle regions physical exam [Werner et al, 2005]. Rotator cuff syndrome was defined as self-reported pain at the shoulder on 2 or more days in the previous month and one of the following on exam: presence of pain with resisted abduction, internal rotation, external rotation, or forward flexion of the shoulder, or tenderness to palpation over the bicipital groove or lateral shoulder.…”
Section: Methodsmentioning
confidence: 99%